Distinct gut microbiota and metabolomic profiles in HBV-related liver cirrhosis: insights into disease progression - Shi, Ke; Sun, Lina; Feng, Ying; Wang, Xianbo (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHepatitis B virus (HBV)-related liver cirrhosis (HBV-LC) is a significant global health issue, affecting gut microbiota (GM) composition and metabolic processes. This study aimed to explore the associations between intestinal microbiota, metabolic profiles, and disease progression in patients with HBV-LC.MethodsFecal samples were collected prospectively from 40 healthy controls (HC) and 83 HBV-LC patients between December 2022 and August 2023. Gut microbiota alterations at various stages of liver function were analyzed using 16S rRNA gene sequencing. Untargeted metabolomics was employed to identify potential biomarkers and metabolic pathways associated with early cirrhosis. Additionally, correlations between bacterial genera, inflammatory markers, and metabolites were investigated.ResultsHBV-LC patients demonstrated a significant reduction in bacterial diversity and relative abundance compared to the HC group. Genera such as Alistipes and Lachnospira were notably depleted, while Fusobacterium and Enterococcus were enriched in patients with Model for End-Stage Liver Disease (MELD) scores ≥ 21 or Child-Turcotte-Pugh C grade. Correlation analyses revealed strong associations between intestinal flora, clinical indicators of disease severity, and inflammatory factors. Metabolic analysis showed decreased levels of tocopherol and 21-hydroxypregnenolone, which were strongly linked to the reduced abundance of Alistipes and Lachnospira. Biosynthesis of unsaturated fatty acids and linoleic acid metabolism emerged as critical enrichment pathways.ConclusionsHBV-LC patients displayed significant alterations in gut microbiota and fecal metabolites, which correlated closely with disease severity and inflammatory status. These findings provide new insights into cirrhosis pathogenesis and suggest potential biomarkers for early diagnosis and disease monitoring.